To Probiotic or Not to Probiotic: A Metagenomic Comparison of the Discharge Gut Microbiome of Infants Supplemented With Probiotics in NICU and Those Who Are Not - Jacob A. F. Westaway; Jacob A. F. Westaway; Roger Huerlimann; Roger Huerlimann; Roger Huerlimann; Yoga Kandasamy; Yoga Kandasamy; Catherine M. Miller; Robert Norton; Robert Norton; David Watson; Sandra Infante-Vilamil; et al. (Frontiers Media S.A., 2022)
BackgroundPreterm birth is associated with the development of both acute and chronic disease, and the disruption of normal gut microbiome development. Recent studies have sought to both characterize and understand the links between disease and the microbiome. Probiotic treatment may correct for these microbial imbalances and, in turn, mitigate disease. However, the criteria for probiotic supplementation in NICU's in North Queensland, Australia limits its usage to the most premature (<32 weeks gestation) and small for gestational age infants (<1,500 g). Here we use a combination of amplicon and shotgun metagenomic sequencing to compare the gut microbiome of infants who fulfill the criteria for probiotic-treatment and those who do not. The aims of this study were to determine if probiotic-supplemented preterm infants have significantly different taxonomic and functional profiles when compared to non-supplemented preterm infants at discharge.MethodsPreterm infants were recruited in North Queensland, Australia, with fecal samples collected just prior to discharge (36 ± 0.5 weeks gestation), to capture potential changes that could be probiotic induced. All samples underwent 16S rRNA gene amplicon sequencing, with a subset also used for shotgun metagenomics. Mixed effects models were used to assess the effect of probiotics on alpha diversity, beta diversity and taxonomic abundance, whilst accounting for other known covariates.ResultsMixed effects modeling demonstrated that probiotic treatment had a significant effect on overall community composition (beta diversity), characterized by greater alpha diversity and differing abundances of several taxa, including Bifidobacterium and Lactobacillus, in supplemented infants.ConclusionLate preterm-infants who go without probiotic-supplementation may be missing out on stabilizing-effects provided through increased alpha diversity and the presence of commensal microbes, via the use of probiotic-treatment. These findings suggest that late-preterm infants may benefit from probiotic supplementation. More research is needed to both understand the consequences of the differences observed and the long-term effects of this probiotic-treatment.